Analysis of Light Propagation in Identical and Non-Identical Multicore Photonic Crystal Fibers - K. Ahmad, Ahmad; Mohammed, Miami (Al-Nahrain Journal of Science, 2020)
Multicore photonic crystal fibers (MPCF) with identical and non-identical cores are analyzed numerically using Comsol Multiphysics software. Investing coupling between cores limiting by parameters, such as the slight change in central core diameter; the separation distance between cores and the wavelength were investigated. Controlling these parameters allows predicting the mode propagation. Moreover, anisotropy in all cores diameters of multicores photonic crystal fibers, as a result, the change of all core diameters simultaneously lead to different of coupling behavior, suppresses the coupling between the core modes by inducing a small mismatch between the modes such that the core modes to be uncoupled through this change. Then this leads to the light mode propagate independently of their neighbors and gives rise to the mode to primarily remain in a certain region of the MPCF array. These properties suggest that multicore PCFs could be a novel candidate for both multiplex or de-multiplex.